BIBLIOMETRIC ANALYSIS IN DIMENSION DATABASES FOR SUSTAINABILITY REPORTING RESEARCH - Muthmainnah Muthmainnah; Mursalam Salim; Septyana Prasetianingrum; Yaya Sonjaya (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2024)
This study aims to locate publications on sustainability reporting and outline the features of the studies. This study employed bibliometric analysis to investigate the features of Sustainability Reporting publications and to identify research trends. Numerous databases from dimensions are used to gather publications about sustainability reporting, which are then processed through Vosviewer for analysis and evaluation, and format data RIS and CSV are described with a pivot table. The publications are analyzed and evaluated according to author keyword co-occurrences, country, institutional, journal, and bibliographic pairs. In the last 25 years, 1884 studies were chosen based on the study criteria (1999 - 2024). The United Kingdom is the leading country in the field of sustainability reporting sustainability (based on the name of the journal); Schaltegger and Zvezdov (2015) publications; and Warren Maroun (2018) (based on authors). One term that keeps coming up in discussions about this subject is sustainability reporting. The ESG (environmental, social, and governance) disclosure studies emerged from advances and improvements in sustainability reporting research.